Large scale land investments: Impact on child health - Jana Brandt (Philipps-University Marburg, School of Business and Economics, 2017)
This paper investigates the impacts of large scale land investments on the health of children. I use household data of the 2005 and 2011 Demographic Health Surveys (DHS) for Ethiopia and combine them with information of large scale land investment projects provided by the Land Matrix Observatory. This data provides information about the location of the land investments and about the location of children. With this information I develop an index that indicates the level of investment intensity for each child's residential area. Taking advantage of the repeated cross sectional structure of the DHS data, I estimate the effect of an increase in the investment intensity of a child's residential area and how this effect changes over time. The results indicate that the effect is negative for children born between 2000-2005, but it rises over time by getting less negative or even positive for children born between 2006-2011. The difference-in-differences estimation with Gaussian kernel propensity score matching shows a benefit in the development status of children that are exposed to large scale land investments. This paper investigates the impacts of the recent wave of large scale land investments on the health of Ethiopian children that are exposed to such investments. I use household data of the 2005 and 2011 Demographic Health Surveys (DHS) for Ethiopia and combine them with information of large scale land investment projects provided by the Land Matrix Observatory. This data allows to identify the location of the land investments as well as the location of children born between 2000-2011. I use these information to construct an index that indicates the level of investment intensity for each child's residential area. Taking advantage of the repeated cross sectional structure of the DHS data, I estimate the effect of an increase in the investment intensity of a child's residential area and how this effect changes over time. The results indicate that the effect is negative for children born between 2000-2005, but it rises over time by getting less negative or even positive for children born between 2006-2011. The difference-in-differences estimation with Gaussian kernel propensity score matching shows a benefit in the development status of children that are exposed to large scale land investments.
Keywords: I15; O12; Q15; 330; Large scale land investment; Child health; Development